Synthesis, biological and antioxidant activity of new diamides derived from sulfonamide drug and local anesthesia - Rebaz Jawhar Qadr; Lana H. Chawshli (Zanco Journal of Pure and Applied Sciences, 2023)
A new series of sulfa drug diamides and local anesthesia diamides (2a-f) and (3a-f) have been prepared through the nucleophilic acyl substitution reaction. The pharmacological profile of all newly synthesized compounds was evaluated in vitro for their antibacterial and antifungal activities using the micro broth dilution assay method and antioxidant activity by the DPPH-radical scavenging method. It was revealed that synthesized compounds were exhibiting promising radical scavenging activity and pharmacological activities against both strains. The structures of synthesized diamides were expounded and elucidated on the bases of their FT-IR, 1H- and 13C –NMR spectral data.